HUBUNGAN PENGALAMAN PRAKTIK KERJA INDUSTRI DAN PRESTASI BELAJAR KEJURUAN DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII TKR SMK COKROAMINOTO 2 BANJARNEGARA TAHUN PELAJARAN 2015/2016 - Bayu Sandhi Pamungkas; Pairun Roniwijaya (Jurnal Taman Vokasi, 2016)
The Relationship of Practices Industry Experience and Vocational Learning Achievement with Interest in Entrepreneurship Class XII TKR student of  SMK Cokroaminoto 2 Banjarnegara  academic year 2015/2016. Thesis Study Program of Mechanical Engineering Faculty of Teacher Training and Educational Sciences Sarjanawiyata Tamansiswa University Yogyakarta 2016.The purpose of this research is: (1) to determine the relationship of Industry Experience Working Practices with interest in entreprenuership class XII TKR student of SMK Cokroaminoto 2 Banjarnegara academic year 2015/2016; (2) to determine the relationship of vocational learning achievement with interest in entrepreneurship class XII TKR student of  SMK Cokroaminoto 2 Banjarnegara  academic year 2015/2016; (3) to determine the relationship of Industry Experience Working Practices and Vocational Learning Achievement with Interest in Entrepreneurship Class XII TKR student of  SMK Cokroaminoto 2 Banjarnegara  academic year 2015/2016.This research is ex post facto, as the population of this research is students of class XII TKR SMK Cokroaminoto 2 Banjarnegara academic year 2015/2016 as many as 139 students, sample of research take 100 students. Collecting data using questionnaires and documentation. Data were analyzed using descriptive analysis and prerequisite analysis test, normality test, linearity test and  multicolinearity test. Hypothesis testing using  regression analysis technique.Results of this research is: (1) Industry experience working practices positively and significantly related with interest in entreprenuership class XII TKR student of SMK Cokroaminoto 2 Banjarnegara academic year 2015/2016; (2) Vocational learning achievement positively and significantly related with interest in entrepreneurship class XII TKR student of SMK Cokroaminoto 2 Banjarnegara academic year 2015/2016; (3) Industry experience working practices and vocational learning achievement  together positively and significantly related with interest in entrepreunership class XII TKR student of SMK Cokroaminoto 2 Banjarnegara academic year 2015/2016